초중등학교에서 수학교육체계와 연계된 컴퓨터 프로그래밍 교육과정과 교수방법 - 박영미(Young-Mi Park); 유관희(Kwan-Hee Yoo) (한국콘텐츠학회논문지, 2008)
In the $7^{th}$ education curriculum, computer education curriculum in the elementary and secondary schools is composited into the contents for the use of computers so that there are some limitations in teaching students the abilities for solving various problems of several areas using computers. Recently, the research has done to change the computer education curriculum for enhancing creativity and problem solving ability required by the future education. The contents of the main subject for enhancing them is of computer programming, however, there was not enough research on systematic programming education curriculum for leading to motivating learners and enhanced knowledge transfer to those learners. In this paper, we analysis the contents mathematics education curriculum with consecutive contents and in tight connection with computer education and then extract its programming related elements. Based on those, we propose a programming education curriculum with which we can teach systematically computer programing according to continual and systematic guidance in the elementary and secondary schools. And we develop a teaching model and learning guidance for teaching students programming methods with the computer programming education curriculum proposed in this paper. 제 7차 교육과정에서 초 중등학교의 컴퓨터교육과정이 컴퓨터 활용 중심 내용으로 편성되어 컴퓨터를 이용한 다양한 분야의 문제를 해결할 수 있는 능력을 가르치는데 한계가 있다. 최근 들어 초.중등학교에서 미래 교육이 요구하는 창의적이며 논리적인 사고력과 문제해결력을 신장할 수 있도록 컴퓨터 교육 과정을 변화시키는 연구들이 진행되고 있다. 이러한 능력을 신장시키기 위해 필수적인 교과목의 내용이 컴퓨터 프로그래밍이지만 아직까지 학습자의 학습 동기와 학습 전이를 높일 수 있는 체계화된 프로그래밍 교육과정에 대한 연구가 미흡하다. 본 논문에서는 초 중등학교에서 컴퓨터 교육과 밀접한 관련이 있으면서 교과 내용의 연계성을 갖추고 있는 수학교육과정 내용을 분석하여 프로그래밍 관련 요소를 추출한 후, 이를 기반으로 초 중등학교에서 연속적이고 계열적 내용에 따라 컴퓨터 프로그래밍을 체계적으로 가르칠 수 있도록 프로그래밍 교육 과정을 제시한다. 그리고 본 논문에서 제안한 컴퓨터 프로그래밍 교과과정을 이용하여 프로그래밍 기법을 가르치기 위한 수업 모형과 학습지도안을 개발한다.